Carbonyl flavor compound-targeted colorimetric sensor array based on silver nitrate and o-phenylenediamine derivatives for the discrimination of Chinese Baijiu. (15th March 2022) - Wu, Meixia; Chen, Hengye; Fan, Yao; Wang, Songtao; Hu, Ying; Liu, Jian; Shen, Caihong; Zhou, Chunsong; Fu, Haiyan; She, Yuanbin
Highlights: A sensor array based on the reaction between AgNO3 and OPDs was first proposed. A novel colorimetric sensor for carbonyl flavor compounds and baijiu was proposed. The influence of ethanol is accurately ruled out. PCA and LDA were used to classify all the CFCs and baijius. The taste activity value of CFCs based on the array was first proposed. Abstract: Baijiu is a distilled liquor of great importance in the food industry. Various aroma types, brands, and grades of Baijiu have filled the market; thus, discrimination for quality control is required. Herein, we constructed a novel colorimetric sensor array based on the redox reaction between silver nitrate and o-phenylenediamine or its derivatives for the discrimination of carbonyl flavor compounds (CFCs) and Baijius. The specific colored products were changed by CFCs depending on the influence of silver nanoparticle aggregation and chemical reactions. The array was used to qualitatively and quantitatively identify 21 CFCs with fast response (<14 min), wide linear range (0.025–25 mmol/L), and low detection limits (<60 μmol/L, 29 nmol/L for carboxylic acids). Finally, the array was successfully applied to the discrimination of 56 Baijius. The method proposed in this study is simple, fast, reliable, and has good application potential for the visual determination of Chinese Baijiu.